Strona 1 z 1

Indukcja matematyczna

: 19 mar 2022, 13:09
autor: Pani098_
Wykaż, że dla \(n\) należących do naturalnych zachodzi:
\[ \sum_{k=n+1}^{2n}\frac{1}{k}= \sum_{k=1}^{2n}\frac{(-1)^{k-1}}{k} \]

Re: Indukcja matematyczna

: 19 mar 2022, 13:59
autor: Icanseepeace
Dla \( n = 1 \) mamy:
\( L = \sum\limits_{k=2}^2 (\frac{1}{k}) = \frac{1}{2} = 1 - \frac{1}{2} = \sum\limits_{k = 1}^2 (\frac{(-1)^{k-1}}{k}) = P \)
Założenie:
\( \sum\limits_{k = n+1}^{2n} (\frac{1}{k}) = \sum\limits_{k=1}^{2n} (\frac{(-1)^{k-1}}{k}) \)
Teza:
\( \sum\limits_{k = n+2}^{2n+2} (\frac{1}{k}) = \sum\limits_{k=1}^{2n+2} (\frac{(-1)^{k-1}}{k}) \)
Dowód:
\( L = \sum\limits_{k = n+2}^{2n+2} (\frac{1}{k}) = \sum\limits_{k = n+1}^{2n} (\frac{1}{k}) + \frac{1}{2n+2} + \frac{1}{2n + 1} - \frac{1}{n+1} = \sum\limits_{k=1}^{2n} (\frac{(-1)^{k-1}}{k}) + \frac{1}{2n + 1} - \frac{1}{2n + 2} = \sum\limits_{k=1}^{2n + 2} (\frac{(-1)^{k-1}}{k}) = P \)